The Spanish conflict (circular)
1936-08-13 014_0029_001 NATIONAL COUNCIL OF LABOUR TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1 TRADES UNION CONGRESS Secretary: Sir Walter M. Citrine (Victoria 9820) THE LABOUR PARTY Secretary: J.S. Middleton (Victoria 8016) PARLIAMENTARY LABOUR PARTY Secretary: H. Scott Lindsay (Whitehall 6240) Private and Confidential August 13th, 1936. To the Members of the General Council of the Trades Union Congress and the Executive Members of the Labour Party. Dear Colleague, THE SPANISH CONFLICT (1) It is felt desirable that you should be informed as to the developments which have taken place since the last meetings of the General Council and the Executive Committee of the Party on July 22nd. (2) On Saturday, July 25th, consultation took place between the officers as to the institution of a Fund, in aid of the Spanish Workers' cause. It was decided that an Appeal should be issued immediately under the auspices of the National Council of Labour, on behalf of the "International Solidarity Fund", the results of the Appeal to be specially earmarked for the relief of distress, and the Fund administered through the Labour and Socialist International and the International Federation of Trade Unions, in consultation with our Spanish comrades. (3) It was felt that the success of the Appeal would be largely assured by the making of a substantial grant from national funds at the outset. Members of the Finance and General Purposes Committee of the T.U.C. were approached and agreed that a grant of £1,000 should be made. The appeal was published on Monday, July 27th. (4) During the week-end a Joint Meeting of the Bureau of the Labour and Socialist International and of the Executive of the International Federation of Trade Unions was hastily summoned, and was held at Brussels on the morning of July 28th, 1936. Sir Walter Citrine and Mr. Gillies attended. (5) Mr. Schevenels, who was in touch with representative Spanish comrades in Paris, introduced the discussion by communicating information which he had obtained. The problem of material assistance was discussed in all its aspects, including the sending of Ambulances and Medical Supplies, and the opening of Relief Depots in Spain. 292/946/14/29(i)